Validity and reliability study of the survival roles of children of alcoholics scale - Küliğ, Derya; Engin, Esra (Journal of Dependence, 2017)
Objective: The aim of this methodological study was to determine the validity and reliability of “The Survival Roles of Children of Alcoholics Scale” developed by Devine and Braithwaite (1993) to evaluate the psychosocial status of adolescents that have alcohol-dependant parents, in Turkish population.Material and Method: A total of 277 adolescents between 12 and 24 years of age, who have alcoholdependent parents and referred to Dependency Polyclinic of Ege University Hospital and in Dependency Polyclinic of Manisa Mental Health and Diseases Hospital between 1 March 2014 and 1 July 2015, and who met the inclusion criteria of research and accepted to participate in research comprised the sampling of research. “Introductory Information Form” and “The Survival Roles of Children of Alcoholics Scale” were used as data collection tools.Results: A factor analysis was carried out for the scale’s structural validity study; and five factors consistent with the original scale were identified. In the reliability study, total score correlations were scrutinized, the item total score correlations were found significant over p
Keywords: Alcohol dependency; parent-alcoholism; validity; reliability